To reduce the maximum stress and the stress shielding effect around a dental implant–bone interface using radial functionally graded biomaterials. Issue 7 (19th May 2017) - Asgharzadeh Shirazi, H.; Ayatollahi, M. R.; Asnafi, A.
Abstract: In a dental implant system, the value of stress and its distribution plays a pivotal role on the strength, durability and life of the implant–bone system. A typical implant consists of a Titanium core and a thin layer of biocompatible material such as the hydroxyapatite. This coating has a wide range of clinical applications in orthopedics and dentistry due to its biocompatibility and bioactivity characteristics. Low bonding strength and sudden variation of mechanical properties between the coating and the metallic layers are the main disadvantages of such common implants. To overcome these problems, a radial distributed functionally graded biomaterial (FGBM) was proposed in this paper and the effect of material property on the stress distribution around the dental implant–bone interface was studied. A three-dimensional finite element simulation was used to illustrate how the use of radial FGBM dental implant can reduce the maximum von Mises stress and, also the stress shielding effect in both the cortical and cancellous bones. The results, of course, give anybody an idea about optimized behaviors that can be achieved using such materials. The finite element solver was validated by familiar methods and the results were compared to previous works in the literature.